Islamic Behavior Finance: Literature Review - Herry Ramadhani (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2019)
The purpose of this research to analyze the existing literature on Behavior Finance and Islamic Behavior Finance which can contribute to future studies in the field of Islamic Behavior Finance. This research is based on a critical review of Islamic Behavior Finance. Research findings that there are two different directions between Behavior Finance and Islamic Behavior Finance, further research is needed to develop and find new theories to advance knowledge in the field of Islamic Behavior Finance that can provide information for a Muslim to invest in accordance with sharia principles and provide a broader insight into investment in terms of psychology or behavior.Keywords: Investment, behavior Finance, Islamic Behavior Finance, Sharia and Psychology